2023
DOI: 10.1021/acsami.3c02571
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Large-Area Slot-Die-Coated Perovskite Solar Cell Performance and Reproducibility by Acid-Based Sulfono-γ-AApeptide

Seid Yimer Abate,
Ziqi Yang,
Surabhi Jha
et al.

Abstract: Homogeneous and pinhole-free large-area perovskite films are required to realize the commercialization of perovskite modules and panels. Various large-area perovskite coatings were developed; however, at their film coating and drying stages, many defects were formed on the perovskite surface. Consequently, not only the devices lost substantial performance but also their long-term stability deteriorated. Here, we fabricated a compact and uniform large-area MAPbI 3 -perovskite film by a slot-die coater at room t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…The device fabrication procedures and fitting equations were adopted from the literature. [26] The trap density was calculated using Equation (3).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The device fabrication procedures and fitting equations were adopted from the literature. [26] The trap density was calculated using Equation (3).…”
Section: Resultsmentioning
confidence: 99%
“…Device Fabrication: The FTO patterning and cleaning protocol, [32,[34][35][36][37] and c-TiO 2 layer preparation were adopted from previous literature. [16,26] 0.8 m CsPbI 2.77 Br 0.23 perovskite inks were prepared by mixing 0.208 g CsI, 0.208 g DMAI, 0.306 g PbI 2 , and 0.050 g PbBr 2 with various compositions of eco-friendly solvents, such as dimethyl sulfoxide (DMSO = D), acetonitrile (ACN = A), and 2-Methoxyethanol (2-ME = M). A total of 21 perovskite precursor solutions were prepared.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These cells have achieved a remarkable power conversion efficiency (PCE) of 26.1%, which is comparable to that of single-crystal Si solar cells and surpasses both multicrystalline Si solar cells and Cu­(In,Ga)­Se 2 -based (CIGS) solar cells . Despite these achievements, the development of PSCs with high PCE, low fabrication cost, environmentally friendly materials, long-term stability, and large light-absorbing area, as well as their integration into flexible and sustainable devices, still presents a challenge and has recently emerged as a popular research area. One critical aspect for commercial applications is the fabrication process. Most studies reported in the literature employ thermal evaporation to prepare the top metallic electrodes of PSCs, which require a vacuum atmosphere.…”
Section: Introductionmentioning
confidence: 99%